(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
The acute scarcity of water and the increasing demand for it for various purposes have become a major problem facing most countries suffering from water scarcity and limited water resources. Therefore, monitoring the quality of wastewater discharged into water sources has become an urgent necessity to reduce the pollution of these limited resources. This study used the Wastewater Quality Index (WWQI) method to assess the quality of treated wastewater discharged from the Biological Al Thaghr Treatment Plant into the Tigris River in Basra Governorate, by evaluating the plant’s performance over a full year, 2023. The WQI results showed that only 36.36% of the studied period was the discharged water of good quality. The concentrations of a range of physical and chemical variables in the discharged wastewater to the water body were also compared with the Iraqi standards for this type of water. The results showed that the concentrations of most variables were within the permissible limits, except for a few that exceeded these limits, namely EC, TDS, and CL.